Adaptation, Change and Leadership - Mark Avery (ACHSM, 2022)
The second issue of the journal this year presents publications related to leading and managing within the health sector environment as well as a selection of papers based on presentations made at the recent International Conference on Embracing Change and Transformation. In mobilising and enabling learning, growth and development in health organisations, the important linkages of adaptation, change to the leadership continuum provides both challenges and opportunities....